Alternative Pedagogies and Well-Being: A Systematic Review; [Pegagogías Alternativas y Bienestar: Una Revisión Sistemática] - Pasmanik-Volochinsky, D; Marticorena-Araya, M (Universidad Compultense Madrid, 2024)
This study is a systematic review of literature published from 2018 to June 2022 about wellbeing and subjective wellbeing, and alternative pedagogies, with respect to preschool and school students. It accomplishes the purpose of characterizing research on wellbeing and subjective wellbeing and alternative education in relation to the definitions of wellbeing and subjective wellbeing adhered by articles published found in Scopus and the Web of Science databases. The final sample is composed of 22 articles distributed in two types of alternative pedagogies: Montessori and Forest School. The definition of wellbeing showed various connotations, ranging from its presentation based on preexisting definitions within specialized literature, to its sole mention without further explanation. It is generally understood as socioemotional wellbeing, in both pedagogies, coinciding with one of the distinctive hallmarks of Alternative Education. Subjective wellbeing showed a very reduced presence, associated with preexistent definitions. An increasing number of theoretical and empirical publications about Alternative Education were detected during the last five years, denoting a greater interest for this kind of education and its possibilities. These results show the convenience of continuing development of research in this subject. © 2024, Universidad Compultense Madrid. All rights reserved.